Injury rate and injury patterns in FIS world cup alpine skiing: Have the new ski regulations made an impact? - Haaland, B.; Steenstrup, E.; Bere, T.; Bahr, R.; Nordsletten, L. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Background: New regulations for ski equipment were implemented prior to the 2012/2013 season in the International Ski Federation (FIS) Alpine World Cup (WC). Objective: To investigate the effect of the new ski regulations on the rate and pattern of injuries by comparing data before (2006-2012) and after (2012-2015) the implementation. Methods: Injuries were recorded on the basis of the FIS Injury Surveillance System (FIS ISS) through retrospective interviews at the end of each of the nine WC seasons. All acute injuries that required medical attention were registered. Exposure was calculated on the basis of the official result lists. Results: The absolute injury rate (injuries/100 athletes/season) was lower in the three seasons after the new ski regulations compared with the six seasons before (risk ratio (RR) 0.74, 95% CI 0.63 to 0.87). This was also the case for the relative injury rate (injuries/1000 runs) (RR 0.76, 95% CI 0.59 to 0.98). However, these changes were only evident for male skiers, not for female skiers. There was a lower absolute injury rate for upper body injuries (RR 0.56, 95% CI 0.43 to 0.77), while no difference was found for lower extremity injuries (RR 0.84, 95% CI 0.70 to 1.01). Conclusions: We found a lower rate of injuries in the three seasons after the new ski regulation compared with the six seasons before. However, the ability to draw conclusions on the effects of the equipment change in subgroups of sex, discipline or body part is restricted by the limited statistical power. ABSTRACT FROM AUTHOR